Optimasi Kondisi Fisik Pemain Bola Voli: Latihan Kelincahan dan Koordinasi - Deke , Kristin; Nasriandi, Nasriandi; Nur, Suaib (Jurnal Porkes, 2025)
This study aims to determine the effect of agility and coordination training on optimizing the physical condition of volleyball players. This study uses a quantitative descriptive method with a two group pretest-posttest pre experiment approach. The sample in the study was the entire population, namely 12 Cendrawasih volleyball club players. The average pretest value of group A is 13.67, group B has an average value of 14.33. While the average posttest value of group A is 14.33, group B has an average value of 21.83. Furthermore, based on the results of the IBM SPSS 22 test, the normality test of the pretest and posttest results of group A obtained each Sig value. 0, 415 > 0.05 and Sig. 0,415 > 0,05. The pretest and posttest results of group B obtained a significance value of 0.493 > 0.05 and 0.425 > 0.05, respectively. This means that the research data is normally distributed paired sample test. Pair 1 obtained a Sig. (2-tailed) of 0.000 < 0.05. Pair 2 obtained a Sig (2-tailed) value of 0.002 < 0.05 Homogeneity test of group A posttest data and group B posttest data 0.605 > 0.05 This means that there is an effect of agility training on physical condition. Independent sample T-Test test obtained Sig value. (2-tailed) of 0.843 > 0.05, meaning that there is no difference in the effect of the influence of the physical condition of volleyball players between group A (agility) and group B (coordination).